Deciphering the fibrotic process: mechanism of chronic radiation skin injury fibrosis - Wang, Yiren; Chen, Shouying; Bao, Shuilan; Yao, Li; Wen, Zhongjian; Xu, Lixia; Chen, Xiaoman; Guo, Shengmin; Pang, Haowen; Zhou, Yun; Zhou, Ping (Frontiers in Immunology, 2024)
This review explores the mechanisms of chronic radiation-induced skin injury fibrosis, focusing on the transition from acute radiation damage to a chronic fibrotic state. It reviewed the cellular and molecular responses of the skin to radiation, highlighting the role of myofibroblasts and the significant impact of Transforming Growth Factor-beta (TGF-β) in promoting fibroblast-to-myofibroblast transformation. The review delves into the epigenetic regulation of fibrotic gene expression, the contribution of extracellular matrix proteins to the fibrotic microenvironment, and the regulation of the immune system in the context of fibrosis. Additionally, it discusses the potential of biomaterials and artificial intelligence in medical research to advance the understanding and treatment of radiation-induced skin fibrosis, suggesting future directions involving bioinformatics and personalized therapeutic strategies to enhance patient quality of life.